High Cigarette and Poly-Tobacco Use Among Workers in a Dusty Industry: New Jersey Quarry Workers. Issue 4 (April 2016) - Graber, Judith M.; Worthington, Karen; Almberg, Kirsten S.; Meng, Qingyu; Rose, Cecile S.; Cohen, Robert A.
Abstract : Objective: Tobacco use is high among US extraction and construction workers, who can also incur occupational dust exposure. Information on different types of tobacco use among quarry/mine workers is sparse. Methods: During mandated training sessions, New Jersey quarry workers were surveyed about their tobacco use. Prevalence was calculated for single and multiple tobacco use by demographic and workplace characteristics; logistic regression was used to assess associations with smoking. Results: Two hundred forty (97.1%) workers completed surveys. Among respondents, 41.7% [95% confidence interval (95% CI) 35.4 to 48.3] currently used any tobacco product of whom 28.1% smoked cigarettes. In multivariate analysis, positive associations with smoking included working as a contractor versus mine employee (odds ratio 2.32, 95% CI 1.01 to 5.36) and a usual job title of maintenance (odds ratio 2.02, 95% CI 0.87 to 4.94). Conclusion: Industry-specific information may be helpful in developing targeted tobacco-cessation programs.